Estudo numérico da dinâmica de partículas em secador rotatório não-convencional e sua relação com a desidratação de polpa de acerola - Nunes, Gabriela (2021)
Acerola (Malpighia emarginata DC) is a fruit known for being one of the greatest natural sources of vitamin C, in addition to having other compounds beneficial to human health, being applied not only in the food sector, but also in the pharmaceutical sector. However, the high perishability of the fresh fruit poses challenges in the post-harvest stages, so that an adequate processing is necessary to ensure the use of its nutritional potential. In this sense, the rotary dryer with inert bed is an alternative for preserving acerola pulp, providing products in powder form, with low degradation of bioactive compounds. In this equipment, the inerts are heated by the drying air and the shocks between them promote the fragmentation of the pulp that has dried on the surface of the solids to form the powder. The movement of inert particles occurs due to the presence of flights on the drum's inner walls and this dynamic has a great impact on the dryer's performance. Therefore, this work aimed to study experimentally and numerically the effects of different operational variables on the performance of a rotary dryer with inert bed for the dehydration of acerola pulp. In the numerical study, simulations were performed using the discrete element method (DEM), which provided information on the collision force and the number of particle-particle and particle-wall collisions. These simulations followed 2k factorial designs for different numbers of hangers and had as independent variables the rotation speed and the filling degree of the drum, the fraction between the aggregates of 12.70 and 25.40 mm in diameter, the height and type of hangers. The DEM responses obtained were combined into a single response, based on the desirability function, which allowed the classification of the results of all simulated cases (128) in the range between 0 and 1. From this analysis, it was found that the best combined response corresponded to the geometry current of the dryer (drum with 3 continuous 25 mm high hangers), which proved that the equipment design decisions were appropriate. Also, it was found that high rotation values maximized the collision force and had no significant influence on the number of collisions; while increasing the filling degree favored the number of collisions and had little effect on the collision force. Thus, for the experiments, the variables rotation and drum filling degree were set at the highest numerically explored values. The experimental study began with the physical-chemical characterization of the pulp, which involved, among other analyses, the determination of the contact angle between the acerola pulp – with the addition of different concentrations of a carrier agent (maltodextrin) – and the surface of ceramic inerts. The drying tests were carried out based on a central composite design, which evaluated the effects of the factors drying air temperature, fraction between inerts and maltodextrin concentration, on the drying yield and on the contents of bioactive compounds (phenolics, flavonoids and ascorbic acid). For all the studied conditions, the maximum result of water activity obtained for the produced powders was 0.103, which guarantees the inhibition of microbial activity during storage. The drying yield was positively influenced by the increase in temperature and the fraction between inerts, that is, by the presence of more inerts of smaller diameter; the addition of maltodextrin was beneficial at concentrations close to a medium value. In relation to bioactive compounds, the concentration of maltodextrin was the variable that had the greatest influence, due to the dilution of the other compounds in the food. The multi-response optimization, performed in search of a higher yield and less degradation of bioactive compounds, resulted in a concentration of 6.28% of maltodextrin, a fraction between inerts of 46.19% and a temperature of 77.2°C, and for the experiment carried out in this condition, the best levels of bioactive compounds and a yield of 59.87% were obtained. Therefore, it was concluded that rotary dryer with inert bed was efficient for the dehydration of acerola pulp and has great potential to be industrially exploited, since it produced, with high yields, acerola powders with appreciable characteristics.